Perspectives of civil aircraft avionics development - Наумов, А. В. (Proceedings of National Aviation University (archive), 1999)
Considered are main directions for civil avionics development. General requirements for airborne equipment functions. Analysis of airborne avionics selection per architecture and economical effectiveness in made. Proposed is the necessity of new approach to integrated avionics complex design, first of all, on basis of mathematical method for aircraft equipment and technical characteristics definition